2013
DOI: 10.1637/10341-083112-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Viral Kinetics, Shedding Profile, and Transmission of Serotype 1 Marek's Disease Vaccine Rispens/CVI988 in Maternal Antibody-Free Chickens

Abstract: Probably the most effective current vaccine against Marek's disease is the live Rispens (CVI988) attenuated serotype 1 Marek's disease virus (MDV). It is unknown whether the currently available Rispens vaccines transmit effectively between chickens. To investigate the kinetics and shedding of three commercially available strains of this virus and the extent of lateral transmission, we measured the shedding rate in dander and the viral load in peripheral blood lymphocytes (PBLs) and feather tips over time. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 27 publications
3
25
1
2
Order By: Relevance
“…The replication of CVI988 virus in the feather follicle has been previously reported [22,23] and its shedding attested by the presence of viral DNA in dust [23]. Baigent and al. reported high levels (10 6 to 10 8 ) of CVI988 genome copy numbers per 10 6 feather tip cells, from 10-to 28-day postvaccination in maternal antibody-free SFP chickens [22].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The replication of CVI988 virus in the feather follicle has been previously reported [22,23] and its shedding attested by the presence of viral DNA in dust [23]. Baigent and al. reported high levels (10 6 to 10 8 ) of CVI988 genome copy numbers per 10 6 feather tip cells, from 10-to 28-day postvaccination in maternal antibody-free SFP chickens [22].…”
Section: Discussionmentioning
confidence: 85%
“…Baigent and al. reported high levels (10 6 to 10 8 ) of CVI988 genome copy numbers per 10 6 feather tip cells, from 10-to 28-day postvaccination in maternal antibody-free SFP chickens [22]. Other authors reported titers that never exceeded 10 6 and was below 10 2 at 56 days in maternal antibody-free White leghorn vaccinated at 1 day [23]. Considering that Rispens may be less shed than HVT (especially over time), and that only 20 % of the birds had received Rispens, the absence of GaHV-2 in this analysis is not totally surprising.…”
Section: Discussionmentioning
confidence: 96%
“…Good progress has been made in studying the kinetics of infection with mixed infections of MDV with HVT and MDV-2 vaccines (Islam and Walkden-Brown, 2007;Islam et al, 2006b). For single infections with the Rispens virus the kinetics of viral replication in the early post infection stage in feather tips and lymphocytes has been reported (Baigent et al, 2005b) as have the longer term kinetics in lymphocytes, feather tips and dust, and the efficacy of transmission to unvaccinated chickens (Islam et al, 2013a). With the development of real time quantitative PCR (qPCR) assays which can differentiate between Rispens and pathogenic serotype 1 MDV the possibility of examining the effects kinetics of mixed infections of Rispens and pathogenic MDV became possible.…”
Section: Introductionmentioning
confidence: 99%
“…The genomes of these strains are highly similar to the oncogenic strains, but crucial differences exist . The MD vaccine viruses replicate in host cells and transmit to other birds [Baigent et al, 2005;Islam et al, 2007;Tan et al, 2007;Gimeno et al, 2011;Islam et al, 2013;], but do not induce disease or lymphomas [Calnek and Witter, 1997]. Despite improved understanding of vaccine-related immunity [Witter, 1984;Osterrieder et al, 2006], an explanation for the anti-tumor effect of vaccination has not yet been established.…”
mentioning
confidence: 99%